2021
DOI: 10.21203/rs.3.rs-1087750/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of a Discrete Choice Experiment (DCE) questionnaire to elicit values by pregnant women and decision-makers for the expansion of a NIPS-based prenatal screening program

Abstract: BackgroundIn an accountable world, being able to take into account the value given by relevant stakeholders to an intervention that could be offered to the population is considered as desirable. DCE is an approach particularly suited for the measurement of such values in the field of prenatal care. Yet, DCE studies in the field of prenatal screening have focused mainly on pregnant women and their care providers but have neglected another key actor, the decision-makers. The objective of the study was to develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The development of the DCE questionnaire consisted of sequential mixed methods 16 . We conducted a systematic literature review on the use of DCE in prenatal screening for chromosomal anomalies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of the DCE questionnaire consisted of sequential mixed methods 16 . We conducted a systematic literature review on the use of DCE in prenatal screening for chromosomal anomalies.…”
Section: Methodsmentioning
confidence: 99%
“…The development of the DCE questionnaire consisted of sequential mixed methods. 16 We conducted a systematic literature review on the use of DCE in prenatal screening for chromosomal anomalies. This review identified potential attributes that have been found to influence preferences for undertaking screening tests for new conditions in a NIPS-based prenatal screening program.…”
Section: Dce Developmentmentioning
confidence: 99%